2022
DOI: 10.3390/nu14091729
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutrition and Physical Activity Interventions Provided by Nutrition and Exercise Practitioners for the Adult General Population: A Systematic Review and Meta-Analysis

Abstract: Healthy dietary intake and physical activity reduce the risk of non-communicable diseases. This systematic review and meta-analysis aimed to examine the effect of interventions including both nutrition and physical activity provided by nutrition and exercise practitioners for adults in the general population (those without diagnosed disease). The MEDLINE, CINAHL, Cochrane Central, Cochrane Database of Systematic Reviews and SportDiscus databases were searched for randomized controlled trials (RCTs) published f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 70 publications
1
10
0
2
Order By: Relevance
“…In the present study, it was observed that individuals who practiced physical activity had a better quality of diet compared to sedentary individuals. This finding can be explained by active individuals being more willing to follow healthy eating habits 40 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, it was observed that individuals who practiced physical activity had a better quality of diet compared to sedentary individuals. This finding can be explained by active individuals being more willing to follow healthy eating habits 40 …”
Section: Discussionmentioning
confidence: 96%
“…This finding can be explained by active individuals being more willing to follow healthy eating habits. 40 There are some methodological limitations to be considered in the present study. The main limitation is the use of only one food recall for each participant.…”
Section: Characteristicsmentioning
confidence: 96%
“…Observational studies have linked higher diet quality to reduced prevalence of metabolic comorbidities among people with MS ( 55 , 56 ). Among people without MS, treatments provided by RDNs are effective for weight management and improving lipids, glucose, and blood pressure ( 57 59 ); however, no studies have specifically investigated treatment provided by RDNs among people with MS. A few preliminary dietary intervention trials report improvement in biomarkers of metabolic health ( 60 63 ) suggesting that treatment provided by RDNs would yield similar favorable outcomes among people with MS.…”
Section: Reasons To Include Rdnsmentioning
confidence: 99%
“…Moreover, it is not yet clear whether individual BERN or lifestyle factors can be fundamentally influenced by therapy; this remains a subject of intensive research with sometimes controversial results. At this time, there is strong evidence supporting the positive impact of exercise (E) or physical activity (e.g., Miko et al, 2020 ; Posadzki et al, 2020 ) and nutrition-related (N) interventions (e.g., Rees et al, 2013 ; Naude et al, 2017 ), such as in cardiovascular health (e.g., Casas et al, 2018 ; Fiuza-Luces et al, 2018 ), sometimes also used in combination (e.g., Nitschke et al, 2022 ). Likewise, the evidence supporting a role for primarily cognitive or psychological techniques (B) has improved significantly in recent years, despite methodological weaknesses and the substantial heterogeneity associated with this field of study (reviewed in Esch, 2002 , 2017 , 2020 ).…”
Section: Bern and Resiliencementioning
confidence: 99%